Persepsi Mahasiswa, Pelaku UMKM, dan Masyarakat terhadap Peran Koperasi Merah Putih dalam Penguatan Ekonomi Pembangunan - Aisyah Khairani Lubis; Azza Bunaia; Muhammad Raghid Alfatiy (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to explore the perceptions of students, micro, small, and medium enterprises (MSMEs), and the general public regarding the role of the Merah Putih Cooperative in supporting and strengthening economic development. Cooperatives are recognized as important economic institutions that promote collective welfare, particularly for small-scale entrepreneurs. This research adopts a descriptive survey method, with data collected through questionnaires distributed to 30 respondents representing students, MSME actors, and community members. The data were analyzed using descriptive techniques to capture respondents’ views on the cooperative’s contribution to economic activities. The findings indicate that the majority of respondents perceive the Merah Putih Cooperative as playing a significant and strategic role in supporting the growth of micro-enterprises. The cooperative is considered effective in expanding business networks, facilitating cooperation among members, and contributing to improvements in members’ economic welfare. In addition, respondents believe that the cooperative helps strengthen local economic resilience by encouraging mutual support and shared economic interests. However, the study also reveals several challenges that need to be addressed. Respondents highlighted the need for improvements in service efficiency, organizational management, and access to capital to ensure that the cooperative’s benefits are distributed more evenly. Strengthening institutional capacity, enhancing transparency, and increasing financial accessibility are essential steps to optimize the role of the Merah Putih Cooperative in sustainable economic development.